Freezing and fractionation: effects of preservation on carbon and nitrogen stable isotope ratios of some limnetic organisms. (1st February 2016) - Wolf, J. Marshall; Johnson, Brett; Silver, Douglas; Pate, William; Christianson, Kyle
Abstract : Rationale: Stable isotopes of carbon and nitrogen have become important natural tracers for studying food‐web structure and function. Considerable research has demonstrated that chemical preservatives and fixatives shift the isotopic ratios of aquatic organisms. Much less is known about the effects of freezing as a preservation method although this technique is commonly used. Methods: We conducted a controlled experiment to test the effects of freezing (–10 °C) and flash freezing (–79 °C) on the carbon and nitrogen isotope ratios of zooplankton (Cladocera), Mysis diluviana and Rainbow Trout ( Oncorhynchus mykiss ). Subsamples ( 0.5 mg) of dried material were analyzed for percentage carbon, percentage nitrogen, and the relative abundance of stable carbon and nitrogen isotopes (δ 13 C and δ 15 N values) using a Carlo Erba NC2500 elemental analyzer interfaced to a ThermoFinnigan MAT Delta Plus isotope ratio mass spectrometer. Results: The effects of freezing were taxon‐dependent. Freezing had no effect on the isotopic or elemental values of Rainbow Trout muscle. Effects on the δ 13 C and δ 15 N values of zooplankton and Mysis were statistically significant but small relative to typical values of trophic fractionation. The treatment‐control offsets had larger absolute values for Mysis (δ 13 C: ≤0.76 ± 0.41‰, δ 15 N: ≤0.37 ± 0.16‰) than for zooplankton (δ 13 C: ≤0.12 ± 0.06‰, δ 15 N: ≤0.30 ± 0.27‰). The effects of freezing were more variable for the δ 13 C values of Mysis, and more variable for the δ 15 N values of zooplankton. Generally, both freezing methods reduced the carbon content of zooplankton and Mysis, but freezing had a negative effect on the %N of zooplankton and a positive effect on the %N of Mysis . Conclusions: The species‐dependencies and variability of freezing effects on aquatic organisms suggest that more research is needed to understand the mechanisms responsible for freezing‐related fractionation before standardized protocols for freezing as a preservation method can be adopted. Copyright © 2016 John Wiley & Sons, Ltd.